Diagnostic case study and treatment of Giardiasis in cat at Rvet Clinic Bogor - Risa Tiuria; Hardiyanti, Niken; Akbari, Rizal Arifin (Jurnal Riset Veteriner Indonesia (Journal of The Indonesian Veterinary Research), 2023)
Giardia sp. is a digestive tract protozoan that can cause Giardiasis. This disease is classified as a water-borne parasitic disease. Giardiasis infects cats, especially cats who have a habit of drinking raw water or sewage. This case study aims to learn the treatment given to cats with Giardiasis. The cat in this study was named Memed, a cat with a mixed Persian breed and was 1.5 years old. Memed came to the RVet Bogor clinic with a grievance of diarrhea without blood for six days and was not accompanied by vomiting. The owner explained the cat was often released and drank water carelessly. Memed was diagnosed with Giardiasis after discovering of Giardia cysts in stool samples that were observed using the fecal flotation technique. Memed was given medical therapy using Metronidazole and vitamin B12 preparations. After the 5th post-therapy day, Memed was declared cured of giardiasis, characterized by the consistency returning to normal and no Giardia cysts found in the feces. Keywords: Giardiasis, Cats, Fecal Flotation, Metronidazole